STUDY OF EXPANSIVE SOIL USING PALM OIL FUEL ASH - Jufrimal, Fathin
Several instances of infrastructure damage on various roads in Java, such as the Jatibarang - Karangampel, Semarang - Purwodadi, Wirosari - Cepu routes, and Jakarta - Cikampek Toll Road, are caused by expansive soil. These detrimental effects necessitate soil improvement, one potential method being the use of Palm Oil Fuel Ash, which is a by-product of palm oil mill combustion. The study uses soil from Sukabungah, Jakarta-Cikampek Toll Road STA 28+000, which has a very high expansiveness. Soil stabilization was performed using Palm Oil Fuel Ash at varying percentages of 5%, 7.5%, 10%, and 12.5% with curing times of 0, 7, 14, and 21 days. Test conducted include compaction tests, unconfined compressive strength tests, CBR tests, swelling tests, and methylene blue tests The addition of Palm Oil Fuel Ash to expansive soil has a positive impact, such as increasing soil shear strength and CBR values, with the optimal addition being 5%. Additionally, Palm Oil Fuel Ash is effective in reducing swelling potential, expansion pressure, and methylene blue value, with the optimal addition being 12.5%. However, considering the overall results, the optimal addition is 7.5% of Palm Oil Fuel Ash, which is effective in enhancing shear strength and CBR values and reducing swelling in the soil.